Klekluk! - Garcellano, Lemuel; Cruz, Christian Oliver; Florendo,, Laya Isabelle G. (Quezon City LG & M Corporation, 2013)
"These past few days, Arbi often comes home with bumps and bruises. He says he had a fight with three headed insects, the kleklukS... This book gives life to the touching story of a son's great love for his mother, and the lesson it brings about having courage to accept things one cannot change."
Text in Filipino and English.
Keywords: Children's stories, Philippine (English)